Gender Injustice and The Image of Women in the Novel Cantik itu Luka By Eka Kurniawan - Anik Febrianti Ni Luh (Universitas Nahdlatul Wathan Mataram, 2023)
This study uses a study of feminist literary criticism which focuses on finding out (1) the gender injustice experienced by female characters, (2) the image of women and (3) the relationship between gender inequality and the image of women in the Novel Cantik itu Luka by Eka Kurniawan. The method used is descriptive qualitative, the subject of this research is the novel Cantik is a Wound while the object of research is gender inequality, the image of women and the relation of gender inequality with the image of women. The data obtained from books related to this research both theoretically and factual data from the CIL. Sources of data in this study are in the form of primary data and secondary data with the method of literature. The research instrument used data cards, the data were analyzed using data triangulation. This study found data that supports 3 (three) research focuses, namely gender inequality in the form of two data stereotypes, two data marginalization, two data violence, one data subordination and one data workload. The female image consists of two physical aspects of self-image and two psychological data and two social data. The last data found is the relation of gender inequality with the image of women as many as three data.